Avian Reovirus Protein p17 Functions as a Nucleoporin Tpr Suppressor Leading to Activation of p53, p21 and PTEN and Inactivation of PI3K/AKT/mTOR and ERK Signaling Pathways - Huang, Wei-Ru; Chiu, Hung-Chuan; Liao, Tsai-Ling; Chuang, Kuo-Pin; Shih, Wing-Ling; Liu, Hung-Jen (PloS one, 2015)
Avian reovirus (ARV) protein p17 has been shown to regulate cell cycle and autophagy by activation of p53/PTEN pathway; nevertheless, it is still unclear how p53 and PTEN are activated by p17. Here, we report for the first time that p17 functions as a nucleoporin Tpr suppressor that leads to p53 nuclear accumulation and consequently activates p53, p21, and PTEN. The nuclear localization signal (119IAAKRGRQLD128) of p17 has been identified for Tpr binding. This study has shown that Tpr suppression occurs by p17 interacting with Tpr and by reducing the transcription level of Tpr, which together inhibit Tpr function. In addition to upregulation of PTEN by activation of p53 pathway, this study also suggests that ARV protein p17 acts as a positive regulator of PTEN. ARV p17 stabilizes PTEN by stimulating phosphorylation of cytoplasmic PTEN and by elevating Rak-PTEN association to prevent it from E3 ligase NEDD4-1 targeting. To activate PTEN, p17 is able to promote β-arrestin-mediated PTEN translocation from the cytoplasm to the plasma membrane via a Rock-1-dependent manner. The accumulation of p53 in the nucleus induces the PTEN- and p21-mediated downregulation of cyclin D1 and CDK4. Furthermore, Tpr and CDK4 knockdown increased virus production in contrast to depletion of p53, PTEN, and LC3 reducing virus yield. Taken together, our data suggest that p17-mediated Tpr suppression positively regulates p53, PTEN, and p21 and negatively regulates PI3K/AKT/mTOR and ERK signaling pathways, both of which are beneficial for virus replication.